Activity and Expression of Midgut Proteases from Mexican and US Trichoplusia ni (Hübner) Strains Exposed to Bacillus thuringiensis - Iracheta, Maria Magdalena; Oppert, Brenda; Valadéz Lira, José Alberto; Rodríguez Padilla, María Cristina; Tamez Guerra, Patricia (Florida Entomological Society, 2017)
Abstract Proteases in the insect midgut have been associated with differences in susceptibility to Bacillus thuringiensis (Bt) insecticidal toxins. Therefore, we evaluated the protease activity of laboratory versus field strains of Trichoplusia ni that were previously characterized by their susceptibility to Bt Cry toxins or protoxins and antimicrobial peptide production (Tamez-Guerra et al. 2006, 2008). In addition, because aminopeptidases may be involved in Bt resistance, the expression of T. ni aminopeptidase N1 transcript (tnapn1) was analyzed by RT-PCR. These strains included Mexican (NL) and American (US) laboratory strains, as well as a field collected strain (GTO), and strains obtained by XenTari® selection from the laboratory strains (NLX and USX) or field strain (GTOX). The activity of proteases in midgut extracts were evaluated by in vitro assays or in-gel activity with specific substrates. The results indicated that the ratio of midgut protease activity (trypsin:chymotrypsin) was higher in the laboratory NL and US strains, but the differences did not correlate with Bt resistance. The ratio was slightly increased in the Xentari-selected field strain GTOX, and zymograms with Xentari or Cry1Ac as substrates suggested that both high and low molecular mass protease activities were increased in GTOX. Selection also resulted in 87% and 300% higher tnapn1 amplification in Xentari-selected NLX and USX, respectively. The relationship between Bt susceptibility, proteases and tnapn1 expression and activity alterations is discussed. Key Words: trypsin; chymotrypsin; Bt protoxins and toxins activation; aminopeptidase N1; enzymatic alterations